Evaluation of Post-Tonsillectomy Complications between the Traditional Cold-Steel Dissection and Electrocautery Methods. A Controlled Randomized Trial - Allah Noor, Muhammad Mudassir, Saadat Ullah Khan, Shahibzada Fakhar Alam (Pakistan Journal of Medical & Health Sciences, 2023)
Background: One of the most frequent ENT surgical procedures is the tonsillectomy. Comparing electrocautery to the conventional cold-steel dissection technique, it has been indicated that the latter will cause fewer post-tonsillectomy problems. However, there needs to be more randomized controlled studies to compare the two methods. Objectives: This Study’s primary goal is to compare the post-tonsillectomy problems caused by the electrocautery technique versus the conventional cold-steel dissection approach. Methods: Between January 2022 and January 2023, this Study was carried out by the department of Ent hmc Peshawar. A prospective randomized controlled trial will include 125 participants in total. Patients will get a tonsillectomy and be randomly allocated to either the electrocautery technique or the conventional cold-steel dissection approach. Pain, bleeding, and infection related to post-tonsillectomy sequelae will be assessed and compared between the two groups. Results: The Study’s findings will be utilized to compare the effectiveness and safety of the electrocautery approach versus the conventional cold-steel dissection method for tonsillectomy. Conclusion: This Study will provide otolaryngologists with evidence-based advice on a tonsillectomy procedure. Keywords: tonsillectomy, electrocautery, cold-steel, post-tonsillectomy complications, randomized controlled trial